A Cartography of Creativity, Labor, and Identity in Contemporary Higher Education: Review of Patricia Leavy’s (2025) The Artist Academic - Gullion, Jessica Smartt (Art/Research International, 2026)
The Artist Academic is a foundational blueprint for scholars seeking to maintain intellectual freedom and methodological rigor in an area of shifting academic legitimacy. In this review, I discuss the intersection of creative practice, academic labor, and institutional identity in Patricia Leavy’s (2025) The Artist Academic. The book is a critical autoethnography of the artist/academic duality and offers a transparent account of Leavy’s transition from professor to independent scholar. I analyze Leavy’s major contributions across three domains: the negotiation of identity within a corporatized university, her demystification of the publication landscape, and the function of the memoir as a meta-commentary on arts-based research. I also highlight Leavy’s critique of gender scrutiny and the institutional suspicion towards non-traditional research outlets.